Antibiotic prescribing for acute respiratory infections in New York City: A model for collaboration. (18th September 2018) - Guzik, Joan; Patel, Gopi; Kothari, Pooja; Sharp, Misha; Ostrowsky, Belinda
Abstract: Objective: To assess the status of antibiotic prescribing in the ambulatory setting for adult patients with acute respiratory infections (ARIs) and to identify opportunities and barriers for outpatient antibiotic stewardship programs (ASPs). Design: Mixed methods including point prevalence using chart reviews, surveys, and collaborative learning. Setting: Hospital-owned clinics in the New York City area. Participants/Patients: In total, 31 hospital-owned clinics from 9 hospitals and health systems participated in the study to assess ARI prescribing practices for patients >18 years old. Interventions: Each clinic performed a survey of current stewardship practices, retrospective chart reviews of prescribing in 30 randomly selected ARI patients from October 2015 to March 2016, and surveys of provider characteristics and knowledge. Clinics participated in collaborative learning with peers and experts in antibiotic stewardship and collected data from June 2016 to August 2016. Sites received data reports by individual clinic, aggregated by hospital, and were compared among participating clinics. Results: Few sites had outpatient stewardship activities. The retrospective review of 1, 004 ARI patients revealed that 37.3% of ARI patients received antibiotics, with significant variation in prescribing practices among sites (17.4%–71.0%; P <.001). Macrolides were the most commonly prescribed antibiotics. Most of the 302 respondents recognized the need for tools to assist in prescribing. Conclusions: This collaborative study establishes a baseline assessment of the status of outpatient ASPs in New York City. It provides hospitals, health systems, and individual clinics with specific data to inform their development of stewardship interventions targeting ARIs.